On the taxonomy of the tribe Adenissini Dlabola (Hemiptera: Fulgoromorpha: Caliscelidae: Ommatidiotinae), with the description of a new genus and a new species from Vietnam - Gnezdilov, Vladimir M. (Acta entomologica slovenica (Ljubljana), 2008)
Coinquendini Gnezdilov & Wilson, 2006 is downgraded to subtribal level in the tribe Adenissini Dlabola. Delhina eurybrachydoides Distant is redescribed and placed in the subtribe Coinquendina, stat. n., firstly recorded from Nepal. Phusta dantela gen. et sp. n. from Vietnam is described in the subtribe Pteriliina Gnezdilov & Wilson.
Keywords: entomologija; Hemiptera; Nepal; nove vrste; škržati; Vietnam